2015
DOI: 10.11613/bm.2015.003
|View full text |Cite
|
Sign up to set email alerts
|

Advances in urinary protein biomarkers for urogenital and non-urogenital pathologies

Abstract: The discovery of protein biomarkers that reflect the biological state of the body is of vital importance to disease management. Urine is an ideal source of biomarkers that provides a non-invasive approach to diagnosis, prognosis and prediction of diseases. Consequently, the study of the human urinary proteome has increased dramatically over the last 10 years, with many studies being published. This review focuses on urinary protein biomarkers that have shown potential, in initial studies, for diseases affectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 80 publications
0
23
1
Order By: Relevance
“…16 This mechanism is likely to cause collagen fragments detected in patients with atherosclerosis. 17 In this study, the mean concentration of collagen in the treatment group was higher by (1.3 ng/ml) than the mean of the control group (0.23 ng/ml). Measurements were made at week 16 after treatment for the provision of atherogenic diet.…”
Section: Discussioncontrasting
confidence: 43%
See 3 more Smart Citations
“…16 This mechanism is likely to cause collagen fragments detected in patients with atherosclerosis. 17 In this study, the mean concentration of collagen in the treatment group was higher by (1.3 ng/ml) than the mean of the control group (0.23 ng/ml). Measurements were made at week 16 after treatment for the provision of atherogenic diet.…”
Section: Discussioncontrasting
confidence: 43%
“…Other studies show type I collagen is found in cancer patients with bone metastases, the bone metabolic disease, liver abnormalities, and some other chronic inflammation. 17,20 Research conducted by Von Zur Muhlen et al, on mouse ApoE -/ -induced by high-fat diet shows that collagen expression can occur because of the general effect of high-fat diet. (11) Other organ disorders are also affected (kidneys, heart, muscles, lymph nodes, spleen, and liver).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In comparison to blood where proteins tend to be degraded by proteases like thrombin during coagulation, urine proteins are stable because these proteins are secreted mature. Moreover, owing to the availability, ease of collection and frequent correlation with the pathophysiology of diseases [3], it is not at all surprising that urinary proteins have been explored for use as biomarkers for a variety of diseases [4][5][6].…”
Section: Introductionmentioning
confidence: 99%